2021
DOI: 10.3991/ijet.v16i21.25001
|View full text |Cite
|
Sign up to set email alerts
|

The Student-centered STEM Learning Model Based on Artificial Intelligence Project: A Case Study on Intelligent Car

Abstract: Artificial intelligence has become a crucial technology for the development of the times. In the practice of emerging engineering education about artificial intelligence, how to enhance students' understanding of artificial intelligence technology, strengthen students' enthusiasm for learning, and improve their research and application innovation ability is a key issue. This study constructs a student-centered STEM learning model that emphasizes innovative applications, so as to promote project-based learning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Analysing the research devoted to AI-based methodology in higher education, it was found that six teaching approaches are effectively applied. They include: differentiated instruction (Büyüksoy et al, 2020;Eikeland & Ohna, 2022), student-centered approach (Kerimbayev et al, 2023;Liao et al, 2021), technology-based approach (Kozlova & Pikhart, 2021;Zawacki-Richter et al, 2019), group learning (Kim et al, 2022b;Seo at al., 2021;Tan et al, 2022), game-based learning (Priyaadharshini et al, 2020;Videnovik et al, 2023), and competency-based approach (Margienė et al, 2022;Oroszi, 2020). Figure 2 shows the teaching approached in higher education with AI.…”
Section: Research Resultsmentioning
confidence: 99%
“…Analysing the research devoted to AI-based methodology in higher education, it was found that six teaching approaches are effectively applied. They include: differentiated instruction (Büyüksoy et al, 2020;Eikeland & Ohna, 2022), student-centered approach (Kerimbayev et al, 2023;Liao et al, 2021), technology-based approach (Kozlova & Pikhart, 2021;Zawacki-Richter et al, 2019), group learning (Kim et al, 2022b;Seo at al., 2021;Tan et al, 2022), game-based learning (Priyaadharshini et al, 2020;Videnovik et al, 2023), and competency-based approach (Margienė et al, 2022;Oroszi, 2020). Figure 2 shows the teaching approached in higher education with AI.…”
Section: Research Resultsmentioning
confidence: 99%
“…Consequently, Chinese universities have undertaken a transition from traditional teacher-centered methods to studentoriented learning strategies in STEM courses, focusing on active engagement and the application of knowledge (Liu & Cheng, 2005;Zhou, 2016). For instance, Liao et al (2021) proposed a student-centered STEM learning model that integrates real projects, cooperative learning activities, and innovation cultivation to enhance Chinese engineering students' understanding of artificial intelligence technology and foster their enthusiasm for learning. Similarly, Sun and Liu (2021) implemented a student-centered approach, incorporating hands-on projects, in-class quizzes, and one-to-one Q&A sessions in theoretical mechanical lessons at a Chinese university.…”
Section: The Current Studymentioning
confidence: 99%
“…This approach emphasizes deepening learning through real projects and encourages students to apply theoretical knowledge to practical problems. Early research indicated that project-based teaching can enhance students' academic performance and knowledge retention [6]. Additionally, students engaged in projects typically need to collaborate actively, problem-solve, and think across disciplines, which are crucial skills in the workplace [7].…”
Section: Literature Reviewmentioning
confidence: 99%